Real-Time Monitoring and Economic Dispatch of Smart Distribution Grids: High Performance Algorithms for DMS Applications - Vargas, Alberto (2012)
Power distribution networks are changing its traditional operation paradigm, due to the introduction of the smart grid concept, which encompasses, among others, continuous demand variations, as well as continuous dispatch variations of the distributed generation units. The latter may be controllable or non-controllable. This paradigm shift means to switch from a fixed radial operative topology network to a more dynamical configuration, which changes during the day and hour by hour. In this sense, the massive incorporation of new telecontrol and telecommunication technologies allows a dynamic operation in Real-Time (RT) of distribution networks. In order to achieve an optimal network operation, it is required a continuous RT monitoring, control and economic dispatch by means of a smart DMS (Distribution Management System). The named system must count on high performance algorithms and RT information systems. This paper presents three very efficient algorithms (in terms of speed, robustness and accuracy), which are: load estimation, ac power flow, and optimal reconfiguration for loss minimization. Furthermore, these algorithms have been tested in many real and large scale distribution networks for several utilities and have presented remarkable features for its implementation in a DMS for Smart Distribution Grids (SDGs).